Programa bolsa família e a relação com a pobreza, desigualdade social e educação: concepções de educadores paulistas - Wellichan, Viviane (2020)
This research aims to analyze the Sao Paulo State's educators conceptions (including directors, coordinators and teachers) about education, poverty and social inequality, added by the analysis about how Brazilian assistance program called "Programa Bolsa Família - PBF" can change, or not, the scholar life of its beneficiaries. The qualitative research, with explanatory approach, was accomplished by questionnaires with Sao Paulo State's educators who attend the "Education, Poverty and Social Inequality" Course throughout the year of 2018 – which was divided in three blocks: a) How the poverty and the social inequality affect the school’s practices? b) Do you consider that PBF reinforces the poverty and social inequality or can assists the scholar life of their beneficiaries? c) Are the children and teenager’s school access and attendance enough for their formation helps to avoid the vicious circle of poverty and citizenship absence? For codification and categorization of the collected data the IRaMuTeQ software was use to performed the analysis under Bardin perspectives, which were compiled in three categories: 1) Poverty, Social Inequality and the Educator’s practices – and three sub-categories: socioeconomic context: poverty, teaching and learning; the school’s role regarding poverty; and; school’s practices and humanization. 2) The PBF and the beneficiaries’ school trajectory – and two categories: The link between PBF, poverty and Social inequality; and the connection between Education, socioeconomic context and PBF. 3) School’s turnover on poverty situation – and two sub-categories: school’s access and attendance on poverty situation; and, the edge of school’s intervention: the vicious circle of the poverty. Considering the hypothesis, the analysis shows that the educators that attend the research have two main conceptions: the beneficiaries had to have an “individual” effort to overcome the poverty or the PBF really can change their families’ life. Additionally, on deep dive conceptions, is possible to consider two groups of analysis: external or internal school’s perspectives. The external perspective considers the link between the public’s sectors and the access to their services. The internal perspective considers that the drivers of change are included in the school and its actions, being important for school and social life. Those changes are mentioned in common with the students’ emancipation, considering that the emancipation concept was not explicit to the educators.